2017
DOI: 10.1016/j.imlet.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid but not plasmacytoid blood DCs possess Th1 polarizing and Th1/Th17 recruiting capacity in psoriasis

Abstract: Psoriasis is a common inflammatory skin disease and dendritic cells (DCs) play crucial role in the development of skin inflammation. Although the characteristics of skin DCs in psoriasis are well defined, less is known about their peripheral blood precursors. Our aim was to characterize the phenotypic features as well as the cytokine and chemokine production of CD1c myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) in the blood samples of psoriatic patients. Blood DCs were isolated by using a magnetic separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…DCs display their membrane affinity toward lymphocytes in situ by forming rosettes around them 29. As part of the innate immune system, they begin to secrete cytokines and chemokines30 and accelerate regeneration 31…”
Section: The Dermismentioning
confidence: 99%
“…DCs display their membrane affinity toward lymphocytes in situ by forming rosettes around them 29. As part of the innate immune system, they begin to secrete cytokines and chemokines30 and accelerate regeneration 31…”
Section: The Dermismentioning
confidence: 99%
“…Prior psoriasis studies on markers of local inflammation which are associated with an increased risk of CVD include myeloperoxidase, a pro-inflammatory heme protein released by myeloid cells (most likely released into circulation by MPO-producing skin-infiltrating myeloid cells), and resistin, an adipose-tissue derived hormone (most likely from adipose tissue subjacent to psoriasis plaques) [21][22][23][24][25]. In addition, we and others demonstrated that myeloid cells are altered in psoriasis patients, where the number of monocyte-derived suppressor cells (MDSCs) and intermediate (CD14 + CD16 + ) monocytes are increased in psoriasis patients, potentially as a result of similarly disordered myeloid cell release [24,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The mature myeloid DCs migrate to the lymph nodes, where, with the help of cytokines they produce, they induce the differentiation of naïve CD4 + T cells (Th0) into Th17, Th1, or Th22, thus triggering the activity of the adaptive immune system in the inflammatory process of psoriasis 12 . These differentiated CD4 + T cells migrate to the dermis, where, by interacting with the innate immune system cells, they produce their typical inflammatory cytokines 13 .…”
Section: Introductionmentioning
confidence: 99%